Intraperitoneal Administration of AAV9-shRNA Inhibits Target Gene Expression in the Dorsal Root Ganglia of Neonatal Mice. (18th July 2013) - Machida, Akira; Kuwahara, Hiroya; Mayra, Azat; Kubodera, Takayuki; Hirai, Takashi; Sunaga, Fumiko; Tajiri, Mio; Hirai, Yukihiko; Shimada, Takashi; Mizusawa, Hidehiro; Yokota, Takanori
Background: There is considerable interest in inducing RNA interference (RNAi) in neurons to study gene function and identify new targets for disease intervention. Although short interfering RNAs (siRNAs) have been used to silence genes in neurons, in vivo delivery of RNAi remains a major challenge, especially by systemic administration. We have developed a highly efficient method for in vivo gene silencing in dorsal root ganglia (DRG) by using short hairpin RNA-expressing single-stranded adeno-associated virus 9 (ssAAV9-shRNA). Results: Intraperitoneal administration of ssAAV9-shRNA to neonatal mice resulted in highly effective and specific silencing of a target gene in DRG. We observed an approximately 80% reduction in target mRNA in the DRG, and 74.7% suppression of the protein was confirmed by Western blot analysis. There were no major side effects, and the suppression effect lasted for more than three months after the injection of ssAAV9-shRNA. Conclusions: Although we previously showed substantial inhibition of target gene expression in DRG via intrathecal ssAAV9-shRNA administration, here we succeeded in inhibiting target gene expression in DRG neurons via intraperitoneal injection of ssAAV9-shRNA. AAV9-mediated delivery of shRNA will pave the way for creating animal models for investigating the molecular biology of the mechanisms of pain and sensory ganglionopathies.